Exogenous and endogenous antioxidants in osteoporosis risk: causal associations unveiled by Mendelian Randomization analysis - Li, Yuancheng; Qi, Huaqian; Huang, Xin; Lu, Gang; Pan, Huashan (Frontiers in Physiology, 2024)
Background Recent epidemiological studies and animal experiments have highlighted the significant role of oxidative stress in the development of osteoporosis (OP). The provision of antioxidants is widely considered a fundamental strategy to combat free radical-induced stress, inhibit oxidative damage, and potentially reverse the adverse effects of oxidative stress on bone health. However, there is no consensus in the scientific literature regarding the practical effectiveness of antioxidants in OP prevention and treatment. Some studies have not shown a clear connection between antioxidant supplementation and decreased OP risk. Therefore, it is essential to clarify the potential causal relationship between antioxidants and the development of OP.The study utilized the inverse variance weighted (IVW) approach as the primary analytical method in the Mendelian Randomization (MR) framework to investigate the causal effects of five exogenous and six endogenous antioxidants on the risk of OP. To thoroughly assess potential pleiotropic effects and heterogeneity among the data analyzed, the MR-Egger intercept test was employed, and Cochran's Q statistic was calculated.In the evaluation of exogenous antioxidants, single-directional two-sample MR analyses did not reveal any statistically significant relationship between these agents and the risk of OP.Regarding endogenous antioxidants, bidirectional two-sample MR analyses were conducted, which generally indicated that most genetically regulated endogenous antioxidants had no significant association with the onset risk of OP. A significant causal relationship was found 1 Sample et al.between OP and serum albumin levels (β: -0.0552, 95%CI: -0.0879 to -0.0225, p < 0.0011 after Bonferroni adjustment, power = 100%).The research uncovers OP as a possible determinant contributing to a decrement in serum albumin levels, and further suggests a potentially intimate relationship between the downward trajectory of serum albumin concentrations and the advancement of the OP disease process.